Parametric Study On The Effectiveness Of A Novel Flat Truss Shape Punching Shear Reinforcement Using Finite Element Model - Chan, Wai Kit (Universiti Sains Malaysia, 2018)
This research aims to gain understanding of the behaviour of a slab-column model in terms of deformation and stress in the steel reinforcement when subjected to force at the top column surface. The intention is to simulate the punching shear failure of a flat slab in a building using ANSYS Static Structure R14 software. The context of this study is the prevention of punching failure by addition of novel flat truss shaped punching shear reinforcement (FTSPSR) and the effect of varying the number of segments in a truss to the punching behaviour of the slab. A total of five models were constructed for this study. A validation work using ANSYS model (M1) with slab dimension 1050 mm x 1050 mm x 100 mm against past experimental data exhibited good agreement and the overall percentage difference was calculated to be less than 20 %. In order to accommodate the FTSPSR, the thickness of the slab was increased to 150 mm (model M2). The slab-column model having FTSPSR with four segments (model M3) reduced the maximum deflection by approximately 6.02 % compared to model M2. Moreover, the maximum rebar stress at highest applied load was 2.81 % lesser than that of M2. It was also noted that incorporating more truss segment FTSPSR increased the stiffness of the model. This phenomenon is particularly true for model M4 (five segments) and model M5 (six segments) because the maximum deflection was reduced by 5.33 % and 10.57 % respectively for model M4 and M5 compared to model M3. Meanwhile, the maximum rebar stress reduced by 8.19 % and further to 13.01 % for model M4 and M5 respectively when compared to model M3. It can be concluded that the novel FTSPSR has the potential to be used in flat slab construction.